Administration of tropical colonies - Lugard, Frederick John Dealtry 1858-1945; Bruce, Charles, 1837-1920 1837-1920; Lyttelton, Alfred, 1857-1913 1857-1913; Großbritannien. Colonial Office; National Archives (Großbritannien); Adam Matthew Digital (Adam Matthew Digital, 1905)
Colonial Office file containing letters by Sir F.D. Lugard and Sir Charles Bruce and responses by A. Lyttelton, Secretary of State for the Colonies, and a newspaper article, concerning administrative reforms in the West African colonies and the roles of the High Commissioner and Governor